2018
DOI: 10.1103/physrevd.97.075037
|View full text |Cite
|
Sign up to set email alerts
|

Signal to background interference in pptHtWb

Abstract: We investigate in the Large Hadron Collider (LHC) environment the possibility that sizeable interference effects between a heavy charged Higgs boson signal produced via bg → tH − (þc:c:) scattering and þc:c:) and the irreducible background given by bg → tW − bb topologies could spoil current search approaches where the former and latter channels are treated separately. The rationale for this comes from the fact that a heavy charged Higgs state can have a large width, which can also happen for the CP-odd neutr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The current highest priority, in relation to charged Higgs boson searches at the LHC, is to further establish the H + → tb decay channel in the heavy mass region. With this in mind, using the framework of a generic 2HDM [30], we have investigated the possibility of having large interference effects between signals from a heavy charged Higgs boson via bg → tH − → tW − A → tW − bb (and similarly for h and H) and the irreducible background from bg → tW − bb processes. Therein, it was shown that such interference effects can modify any dedicated charged Higgs boson searches where signal and background are treated separately, which is the case for all aforementioned experimental analyses.…”
Section: Jhep10(2020)209mentioning
confidence: 99%
“…The current highest priority, in relation to charged Higgs boson searches at the LHC, is to further establish the H + → tb decay channel in the heavy mass region. With this in mind, using the framework of a generic 2HDM [30], we have investigated the possibility of having large interference effects between signals from a heavy charged Higgs boson via bg → tH − → tW − A → tW − bb (and similarly for h and H) and the irreducible background from bg → tW − bb processes. Therein, it was shown that such interference effects can modify any dedicated charged Higgs boson searches where signal and background are treated separately, which is the case for all aforementioned experimental analyses.…”
Section: Jhep10(2020)209mentioning
confidence: 99%
“…For instance, in the 2HDM-II, the current measurement of BR(B → X s γ) forces the charged Higgs boson mass to be larger than about 580 GeV [23] while in the 2HDM-I one can still obtain a H ± with a mass as low as 100−200 GeV provided that tan β ≥ 2. Note that, in type-II and -Y, if we allow b → sγ measurement at the 3σ level then it would imply a reduction on the charged Higgs bound from 580 GeV down to 440 GeV [24].…”
Section: B Constraints and Benchmark Pointsmentioning
confidence: 99%